Rare Variants in the ADAMTS13 Von Willebrand Factor–Binding Domain Contribute to Pediatric Stroke. (August 2016) - Stoll, Monika; Rühle, Frank; Witten, Anika; Barysenka, Andrei; Arning, Astrid; Strauss, Christina; Nowak-Göttl, Ulrike
Abstract : Background—: Recently, we reported a gene network of ADAMTS (A Disintegrin-like and Metalloprotease with Thrombospondin motifs) genes as central component of the genetic risk contributing to pediatric stroke. ADAMTS13 is a prime example for such a key component as it cleaves von Willebrand factor multimers, reduces platelet adhesion and aggregation, and downregulates thrombus formation and inflammation. Methods and Results—: We characterized the genetic architecture of ADAMTS13 through targeted next-generation sequencing of 48 affected children and their unaffected siblings and identified in total 241 variants (single nucleotide polymorphisms or insertions/deletions) in the ADAMTS13 gene. From these, based on significance in the sibship disequilibrium test ( P <0.05) or protein-altering properties, we selected 21 common variants covering the complete ADAMTS13 gene for genotyping in 270 trios and subsequent association analyses. Transmission disequilibrium testing was performed for affection status and ADAMTS13 activity levels using PLINK and FBAT, respectively. Ten single nucleotide polymorphisms were significantly associated with pediatric stroke ( P <0.05 to P <0.001), 2 of which (rs2285489 and rs28793911) were also significantly associated with ADAMTS13 levels ( P =0.0004 and P =0.0092). The resulting protective haplotype H1.1. (T:U 95.5: 144.4; P =0.0016) is associated with increased ADAMTS13 levels (age-adjusted P =0.0108). Haplotype association using a sliding window approach assigns this association to the ADAMTS13 von Willebrand factor–binding domain ( P =1.2×10 −4 ). Conclusions—: Our data provide a link between the genetic architecture of ADAMTS13, ADAMTS13 levels, and stroke susceptibility. Altogether, these studies render ADAMTS13 an attractive candidate for functional studies and may contribute to personalized diagnosis and treatment options in future. Abstract : Supplemental Digital Content is available in the text.